Pengaruh Tata Kelola, Efisiensi, Manajemen Risiko dan Kinerja terhadap Keberlanjutan BUS Indonesia - Laileny Tulus Karomah; Yulfan Arif Nurohman (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
Indonesian Islamic banking has undergone strategic consolidation through the establishment of Bank Syariah Indonesia (BSI), which controls 46% of the market share with assets of Rp 351.9 trillion as of December 2024. This study analyzes the influence of corporate governance, operational efficiency, risk management, and financial performance on the business sustainability of Islamic Commercial Banks (BUS) during the 2021-2024 period using Legitimacy Theory and Triple Bottom Line as theoretical foundations. The quantitative research method with a causal comparative approach employs Partial Least Square-Structural Equation Modeling (PLS-SEM) on 10 BUS with 40 panel data observations processed using SmartPLS 3.0. Results indicate the model has excellent predictive capability (R² = 0.900; Adjusted R² = 0.889). Operational efficiency has a significant positive effect on business sustainability (β = 1.045; t = 2.452; p = 0.015) with a very large effect size (f² = 4.330), making it the most dominant factor. Corporate governance (β = -0.053; p = 0.541), risk management (β = -0.120; p = 0.336), and financial performance (β = 0.210; p = 0.484) show no significant effect. Findings indicate that BUS business sustainability is more determined by operational efficiency than profitability, with the post-merger transition period requiring adaptation time for governance impact optimization. Strategic implications direct BUS management to accelerate digitalization and resource optimization to achieve optimal economies of scale and strengthen the competitiveness of the national Islamic banking industry.